2020
DOI: 10.1097/mcg.0000000000001362
|View full text |Cite
|
Sign up to set email alerts
|

Low Risk of Progression of Barrett’s Esophagus to Neoplasia in Women

Abstract: Background and Aims: Men are at a higher risk for Barrett’s esophagus (BE) and esophageal adenocarcinoma (EAC), but little is known about BE progression to dysplasia and EAC in women. We performed a retrospective, multicenter cohort study to assess risk of BE progression to dysplasia and EAC in women compared with men. We also investigated comorbidities, medication use, and endoscopic features that contribute to sex differences in risk of BE progression. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
1
4
0
2
Order By: Relevance
“…Our findings with respect to a higher absolute risk of neoplastic progression and shorter time to neoplasia in males than in females are in line with previous results [9,[19][20][21]. These findings suggest that females might benefit less from current surveillance intervals than males.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings with respect to a higher absolute risk of neoplastic progression and shorter time to neoplasia in males than in females are in line with previous results [9,[19][20][21]. These findings suggest that females might benefit less from current surveillance intervals than males.…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that females might benefit less from current surveillance intervals than males. Prolonging surveillance intervals for patients with a low neoplastic progression risk could increase the cost-effectiveness of BE surveillance substantially, which is worth considering given the debatable cost-effectiveness of current surveillance strategies [21][22][23]. However, while the number (and thus costs) of surveillance endoscopies will decrease with prolonging surveillance intervals, the risk of interval carcinoma's will simultaneously increase.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 4097 patients with Barrett esophagus and without dysplasia reported annual rates of progression to esophageal adenocarcinoma of 0.06% (95% CI, 0.01%-0.10%) for short-segment (Barrett esophagus length <3 cm) Barrett esophagus vs 0.31% (95% CI, 0.21%-0.40%) for long-segment (Barrett esophagus length ≥3 cm) Barrett esophagus . In the retrospective, multicenter cohort study of 2145 patients with Barrett esophagus, after adjusting for body mass index, smoking, race, use of aspirin, nonsteroidal anti-inflammatory drugs, and other factors, women had a lower rate of progression to esophageal adenocarcinoma than men (12.7% vs 21.4%; P < .001) at a median of 5.7 years of follow-up …”
Section: Characteristics Associated With Progression Of Barrett Esoph...mentioning
confidence: 99%
“…We observed that SSc patients with BE are at high risk of neoplastic progression, with an incidence rate of HGD/EAC of 2.62% per year. This is significantly higher than the 0.48% per year reported in general NDBE patients [ 3 ] and 0.1% annual risk reported in women [ 4 ]. It is worthwhile to note that our patients were predominantly female non-smokers, which is markedly different from the classic BE patients, who are white males and obese.…”
mentioning
confidence: 54%